Exposure to motor vehicle exhaust and childhood cancer - Feychting, Maria; Svensson, D.; Ahlbom, Anders (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVES ': 'A case-referent study was conducted to test the hypothesis that exposure to motor vehicle exhaust increases the risk of childhood cancer. ' ' METHODS ': 'Data from a study of residential magnetic field exposure and childhood cancer were used. From a population of 127 000 children living within 300 m of transmission lines in Sweden, 142 cases of childhood cancer were identified, including 39 cases of leukemia and 33 cases of central nervous system tumor. Approximately 4 referents per case were selected at random from the study base. The nitrogen dioxide content of the outdoor air was estimated as an indicator of motor vehicle exhaust. The applied methods give the 99th percentile of the nitrogen dioxide content of the outdoor air for 1-h averages over 1 year. ' ' RESULTS ': 'A relative risk estimate of 2.7 [95% confidence interval (95% CI) 0.9–8.5] was found for total cancer at exposure levels of ≥50 µg/m3, related to those with ≤39 µg/m3. At ≥80 µg/m3, the relative risk was estimated at 3.8 (95% CI 1.2–12.1). Elevated, but imprecise risk estimates were found for leukemia and central nervous system tumors. ' ' CONCLUSION ': 'The results indicate an association between childhood cancer and motor vehicle exhaust, although number of cases was small. These findings and the results of previous studies suggest that further studies of the association between motor vehicle exhaust and childhood cancer are warranted.
Keywords: air pollution; benzene; child neoplasms